Apontamentos em relação às formas de tratamento dos negros pela história da educação - Reports relating to the forms of black people’s treatment through the history of education - Fonseca, Marcus Vinícius (Revista História da Educação, 2012)
Resumo Este artigo tem como objetivo reunir parte da bibliografia sobre os negros na historiografia educacional tentando destacar as principais características da produção que ocorre nesta área. Confere destaque a um posicionamento que mais recentemente começa a reivindicar a constituição de uma dimensão particular da historiografia e que deveria se constituir como uma história da educação dos negros. O artigo procura demonstrar os riscos inerentes a este tipo de operação no âmbito da historiografia educacional brasileira e defende a necessidade de uma mudança de postura dos historiadores no sentido de integrar de forma plena os negros à história da educação. Palavras-chave: história da educação; negros; bibliografia; historiografia. REPORTS RELATING TO THE FORMS OF BLACK PEOPLE’S TREATMENT THROUGH THE HISTORY OF EDUCATION Abstract This article has as its aim to assemble a part of the bibliography on black people in the educational historiography attempting to highlight the main features of production that occurs in this field. Attention is given on the position that recently has claimed for aconstitution of a particular dimension of historiography and it should be built as a history of black people education. This paper is also looking for to demonstrate the inner risks related to this sort of operation in the field of Brazilian Educational Historiography and it advocates a need for change in the posture of historians in the sense of integrating the black people to the educational history effectively. Keywords: history of education; black people; bibliography; historiography. APUNTES EN RELACIÓN A LAS FORMAS DE TRATAMIENTO DE LOS NEGROS POR LA HISTÓRIA DE LA EDUCACIÓN Resumen Este artículo tiene como objetivo reunir parte de la bibliografia sobre los negros en la historiografia educacional tratando de destacar las principales características de la producción que ocurre en esta área. Confiere destaque a un posicionamiento que más recientemente comienza a reivindicar la constitución de una dimensión particular de la historiografia y que debería ser constituída como una história de la educación de los negros. El artículo procura demostrar los riesgos inherentes a este tipo de operación en el ámbito de la historiografia educacional brasilera y defiende la necesidad de una mudanza de postura de los historiadores en el sentido de integrar de forma plena a los negros a la historia de la educación. Palabras clave: historia de la educación; negros; bibliografia; historiografia. NOTES SUR LES FORMES DE TRAITEMENT DES NOIRS PAR L’HISTOIRE DE L’ÉDUCATION Résumé Cet article a pour but de réunir une partie de la bibliographie sur les noirs dans l’historiographie de l’éducation afin de mettre en relief les caractéristiques principales de la production dans ce domaine. On observe une position qui commence plus récemment à révendiquer la constitution d’une dimension particulière de l’historiographie c’est à dire une histoire de l’éducation des noirs. L’on cherche à montrer les risques concernant ce type d’opération dans le contexte de l’historiographie de l’éducation brésilienne et on défend la nécessité d’un changement de position des historiens de façon à intégrer pleinement les noirs à l’histoire de l’éducation. Mots-clé: histoire de l’éducation; noirs; bibliographie; historiographie.